Measurement properties of the PBC-40 and PBC-27: a Dutch validation study - Herold J Metselaar; Maren H Harms; Rozanne C de Veer; Adriaan J van der Meer; Geraldine da Silva; Maria C van Hooff; José Willemse; Elaine Utomo (BMJ Open Gastroenterology)
Objective Patients with primary biliary cholangitis (PBC) have an impaired health-related quality of life (HRQoL). Practice guidelines recommend evaluating the HRQoL in all patients with PBC. The aim of this study was to assess the reliability and validity of our Dutch translation of the PBC-40, a PBC-specific measure of the HRQoL.Design The PBC-40 was translated into Dutch following standardised forward–backward procedures. Participants received the Dutch PBC-40 and the RAND-36 (a validated Dutch version of the 36-Item Short Form Health Survey) through postal mail. The PBC-27 is an abridged version of the PBC-40. Internal consistency between the items within the PBC-40/PBC-27 domains was assessed by Cronbach’s alpha. In addition, score distributions were analysed on floor and ceiling effects. Construct validity was assessed by hypotheses testing using Pearson’s correlation between the PBC-40/PBC-27 domains and RAND-36 scales.Results 177 patients with PBC were included. The mean age was 61.1 (SD 9.9) years and the majority of patients was female (n=164, 92.7%). From the 7080 PBC-40 items, 61 items (0.9%) were missing and 342 items (4.8%) were answered with the ‘does not apply’ option. Each PBC-40 domain had a Cronbach’s α of >0.70, with the highest in the domain fatigue (0.95). For the PBC-27, the lowest Cronbach’s α was 0.69. Floor effects were present in three domains (cognition 19.3%, itch 27.0% and social 25.0% (only for PBC-27)). No ceiling effects were observed. All domains were significantly correlated with the corresponding RAND-36 scale(s) (p<0.001 for all). The strongest correlation was between the PBC-40 domain fatigue and the RAND-36 vitality scale (r=−0.834).Conclusion Our findings demonstrate the reliability and validity of the Dutch PBC-40 and PBC-27 for the assessment of the HRQoL in patients with PBC. This PBC-specific measure can be used in Dutch-speaking patients with PBC for both research and clinical purposes.